Features of angioarchitecture of coronal vessels of man - Zrozhevskyy R.S.; Yakovets H.A.; Fominykh T.A. (Морфологія, 2011)
The purpose of work was a study of features arterial angioarchitecture hearts of people of mature age. For the decision of the put purpose of work research es of features of arterial circulation were conducted on 34 anatomic preparations of hearts of men of mature age (21-36 years). The arterial circulation of heart was studied on corrosive preparations on which counted up the amount of branches 1 and 2 orders. All quantitative findings were analysed by variation-statistical methods. As a result of research new classification of fork of arterial vessels of heart was offered on territorial principle and four a r-terial vascular areas (right lateral area, left lateral area, front partition area and back partition area) are selected with the sepa-rate source of circulation (right coronary artery, circumflex the branch of the left coronary artery, front interventricular branch of the left coronary artery and back interventricular br anch of right coronary artery in accordance with the areas indi-cated higher).